OC-031 Using Genome-Wide Studies to Identify Novel Foxm1 Transcription Factor Target Genes in Oesophageal Cancer. (4th June 2013) - Wiseman, E F; Han, N; Ang, Y S; Sharrocks, A S
Abstract : Introduction: The prognosis of oesophageal cancer remains poor with < 10% 5-year survival. Delineating the molecular pathogenesis of oesophageal cancer could inform future research into targeted therapies and may uncover novel biomarkers to aid management decisions. As a transcription factor with important roles in the control of cell cycle transcription, FOXM1 regulates cellular proliferation and chromosome stability. FOXM1 is frequently overexpressed in human cancers and this aberrant expression has been implicated in cancer initiation, progression and resistance to chemotherapy. Overexpression of FOXM1 mRNA and protein has recently been described in oesophageal adenocarcinoma (OAC) tissues. We aim to identify novel gene targets of FOXM1 to better understand the molecular pathogenesis of OAC. Methods: Chromatin immunoprecipitation (ChIP) followed by deep sequencing (ChIP-seq) of FOXM1 binding sites was performed in OE33 OAC cells. FOXM1 binding at target gene promoters was confirmed with ChIP-qPCR studies. Target gene expression in OE33 cells after siRNA-mediated FOXM1 depletion was examined using qRT-PCR and western blotting. Target gene expression in OAC tissues was examined by analysis of microarray gene expression data. Statistical significance ( p )in knockdown studies was calculated by Student's t -test. The Pearson correlation coefficient (r) was used to measure strength of correlation of gene expression. Results: Putative novel FOXM1 targets identified from an existing FOXM1 ChIP-seq dataset in U2OS osteosarcoma cells were validated by ChIP-seq in OE33 cells. A large overlap between the genes bound by FOXM1 in both cell types was observed. Genes with FOXM1 binding in both cell types whose expression was highly correlated with FOXM1 in OAC tissues such as ETV4, SKA2 and NUCKS1 (r = 0.83, 0.84 and 0.72) were analysed further with ChIP-qPCR and FOXM1 knockdown gene expression studies. OE33 cells demonstrated significant FOXM1 binding at the ETV4 promoter and a reduction in ETV4 mRNA in FOXM1 depleted cells was observed compared to control ( p = 0.0006). However, despite highly significant FOXM1 binding at the SKA2 and NUCKS1 promoters the reduction in SKA2 / NUCKS1 mRNA following FOXM1 knockdown was modest and not significant. Conclusion: We have identified ETV4 as a novel FOXM1 target in oesophageal cancer. We found strong correlation with FOXM1 expression in clinical tissues, in vivo FOXM1 binding to its regulatory regions and evidence of regulation by FOXM1 in OE33 cells. Our studies also highlight the importance of validating ChIP-seq data with gene expression analysis since transcription factor binding at gene promoters does not always correlate with transcriptional regulation by that transcription factor. Disclosure of Interest: None Declared